ANALISIS KONDISI KESEHATAN MENTAL TENAGA KESEHATAN SELAMA PANDEMI COVID 19 DI PUSKESMAS DESA LUBUK AMBACANG KECAMATAN HULU KUANTAN KABUPATEN KUANTAN SINGINGI TAHUN 2022 - Roni Saputra; saniya saniya; zulia nanda (Jurnal Keperawatan Abdurrab, 2022)
The COVID-19 virus, which is currently turning into a pandemic and declared a global emergency, is still continuing, threatening anyone who has the potential to experience symptoms of transmission. Extraordinary conditions on a large scale that threaten health conditions including the mental health of medical personnel, especially nurses, continue to occur. Unfortunately, even though nurses have a vital role in treating COVID-19 patients, their welfare is quite neglected. This study aims to determine the Analysis of the Mental Health Condition of Health Workers during the Covid 19 Pandemic at the Lubuk Ambacang Village Health Center, Hulu Kuantan District, Kuantan Singingi Regency. This research design uses descriptive research type. The population in this study were all health workers in Lubuk Ambacang Village, Hulu Kuantan District, amounting to 30 health workers. The sampling technique in this study was using a total sampling technique so that a sample of 30 people was obtained. The research instrument used a questionnaire consisting of 42 questions. The results of the knowledge of pregnant women after the research was carried out, namely the distribution of respondents based on the condition of the mental level of all health workers, most of whom were mentally normal with a total of 9 respondents (30%), it is hoped that nurses are expected to be able to carry out early detection in recognizing and assessing the mentality experienced by pregnant women. a person in dealing with certain situations or new adaptations.